Sustainable Transport and Corporate Sustainability Performance: Moderating Role of Organization Age - Asha’ari, Maryam Jamilah; Daud, Salina (International Journal of Engineering and Technology, 2018)
Sustainability has been seen as a crucial issue that is being faced by many sectors in Malaysia which involves manufacturing sector. The Malaysian government has enhanced manufacturing organizations to apply green practices in the working environment to achieve corporate sustainability performance. In order for an organization to achieve corporate sustainability performance, the practices of the organization in using green technology such as sustainable transport is very important. The aim of this study is to examine the effects of sustainable transport on corporate sustainability performance with the moderating role of organization age. Drawing data from 130 Malaysia chemical manufacturing organizations, the model studies the moderating role of organization age on the sustainable transport and the corporate sustainable performance of the organizations. Partial Least Square (PLS) analysis is used in this study in order to analyze the data and the multistage sampling technique has also been used in this study. The results show that there is a positive relationship between sustainable transport and corporate sustainability performance. The results also suggest that organization age do not moderates the effect of sustainable transport and corporate sustainability performance. In achieving corporate sustainability performance, this study is important as it will guide employees in the manufacturing sector especially in chemical manufacturing organizations to practice the appropriate green practices such as sustainable transport.